Access barriers and ethical challenges of therapeutic decision-making in patients with inflammatory bowel disease and prior malignancy: a case series - Leandro Medeiros, Larissa (2026)
Objectives: To report a case series of patients with inflammatory bowel diseases and a history of malignancy and to analyze how this condition influenced therapeutic decisionmaking presents a challenging scenario. Materials and methods: This was a retrospective observational study analyzing 11 patients with inflammatory bowel disease and malignant neoplasms followed at an inflammatory bowel disease outpatient clinic of a university hospital. Clinical, therapeutic, and oncologic findings are reported descriptively based on medical record review. Results: Seven patients (64%) had ulcerative colitis, and six (55%) were female, with a mean age of 47 years. Extra-intestinal neoplasms predominated. Six patients (55%) received advanced therapy near the time of cancer diagnosis; reintroduction was possible in four cases. Judicial action was required for two patients. Conclusions: Clinical decision-making in patients with inflammatory bowel disease and a history of malignancy is an individualized process, based on multidisciplinary discussion, bioethical considerations, and the most reliable available evidence, even in the face of state-imposed logistical obstacles. Continuous updating of Clinical Protocols and Therapeutic Guidelines is essential to ensure equitable access to the most appropriate and non-harmful treatment for this patient group.